ANEMIA IN CHRONIC KIDNEY DISEASE PATIENTS - Wulan Yuniarti (Journal Health & Science : Gorontalo Journal Health and Science Community, 2021)
Chronic kidney disease (CKD) is one of world health problems because the prevalence that keeps increasing each year. Anemia is one of the major problems in patients with chronic kidney disease. Anemia can occur in patient with CKD because when damaged, the kidney can’t produce enough erythropoietin. The purpose of this article is to determine whether there is a relationship between anemia with CKD. This type of article is a study of literature from various national and international journals. The method used to present, increase knowledge and understanding of the topics discussed by summarizing published material and providing new factual information or analysis from the relevant literature and the comparing the results in articles. The results of the literature study show that there is a relationship between anemia with CKD, which is characterized by a decrease in hemoglobin in CKD patients. The prevalence of CKD according to gender, mostly occurred in men (0,3%) than women (0,2%).In addition, the highest age prevalence was in the age group 75 years (0,6)%. This is related to the risk factor for CKD. To reduce anemia in CKD patients, erythropoiesis stimulating agent therapy can be given which aims to correct anemia renal until the hemoglobin target is achieved.